Interventions for generalized anxiety disorder in older adults: systematic review and meta-analysis. - Gonçalves, D; Byrne, G (2012)
INTRODUCTION: Generalized anxiety disorder (GAD) is one of the most common anxiety disorders in later life, with widespread consequences for individuals and society. OBJECTIVE: To perform a systematic review of the efficacy of controlled interventions for GAD in adults aged 55 years and older. METHOD: Direct search of digital databases and the main publications on aging and iterative searches of the references from retrieved articles. RESULTS: Twenty-seven trials (14 pharmacological, 13 psychotherapeutic) fulfilled the inclusion criteria, reporting results from 2373 baseline participants. There were no differences between trials in their overall quality. Pooled treatment effects for pharmacological (OR=0.32, 95% CI: 0.18, 0.54) and psychotherapeutic (OR=0.33, 95% CI: 0.17, 0.66) trials were similar, with findings in each case favoring active interventions over control conditions. CONCLUSIONS: Older adults with GAD benefited from both pharmacological and psychotherapeutic interventions. Future studies should investigate combined treatment with medication and psychotherapy.